2001
DOI: 10.1016/s0014-5793(01)03125-8
|View full text |Cite
|
Sign up to set email alerts
|

A novel type 2C protein phosphatase from the human fungal pathogen Candida albicans

Abstract: The reversible phosphorylation of proteins, controlled by protein kinases and protein phosphatases, is a critical mechanism by which eukaryotic organisms regulate cellular signal transduction pathways. There are two superfamilies of protein serine/threonine speci¢c phosphatases, the PPP and PPM families, which speci¢cally dephosphorylate serine/threonine residues [1]. The PPP family is comprised of three subtypes of phosphatases, PP1, PP2A and PP2B, which are distinguished by their associated regulatory subuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 6 publications
5
29
0
Order By: Relevance
“…This model is not without precedent in the PP2C phosphatase family; the catalytic subunit of bovine mitochondrial pyruvate dehydrogenase phosphatase displays a K m for magnesium that increases in the presence of its regulatory subunit (47). However, the K m value for Mn 2ϩ of RsbU, of RsbU in the presence of RsbT, and of the C-terminal domain of RsbU alone were found to be 0.96 mM in all three cases (data not shown) and thus similar to that observed for other PP2C phosphatases (48,49). It would therefore seem unlikely that RsbU is regulated by changes in the K m for its requisite co-factor.…”
Section: A Comparison Of Rsbt Binding By N-rsbu-(1-84) and N-rsbu-(1-supporting
confidence: 81%
“…This model is not without precedent in the PP2C phosphatase family; the catalytic subunit of bovine mitochondrial pyruvate dehydrogenase phosphatase displays a K m for magnesium that increases in the presence of its regulatory subunit (47). However, the K m value for Mn 2ϩ of RsbU, of RsbU in the presence of RsbT, and of the C-terminal domain of RsbU alone were found to be 0.96 mM in all three cases (data not shown) and thus similar to that observed for other PP2C phosphatases (48,49). It would therefore seem unlikely that RsbU is regulated by changes in the K m for its requisite co-factor.…”
Section: A Comparison Of Rsbt Binding By N-rsbu-(1-84) and N-rsbu-(1-supporting
confidence: 81%
“…Jiang and coworkers (41) demonstrated that CaPtc7 has the biochemical characteristics of classical PP2C enzymes (i.e., Mn 2ϩ -and Mg 2ϩ -dependent in vitro phosphatase activity blocked by NaF but not sensitive to okadaic acid). The Nterminal region of CaPtc7 contains a transmembrane domain and a potential mitochondrion-targeting signal that justifies its presence in this organelle (41,107). Homologues of CaPtc7 can be found in S. cerevisiae (Fig.…”
Section: Downloaded Frommentioning
confidence: 99%
“…Furthermore, a deletion mutant of cnb1, which encodes a regulatory subunit of calcineurin, has significantly attenuated virulence in a mouse model of C. albicans infection (6). Other C. albicans genes identified as protein phosphatases include CDC14 (13), CYR1 (24,36), CPP1 (14), PTC7 (25), SIT4 (34), and YVH1 (21). SIT4 and YVH1 have been implicated in the control of virulence-related genes.…”
mentioning
confidence: 99%